Application of Head Up 30 Degree Positioning to Improve Oxygen Saturation in Stroke Patients in the Emergency Room of Pandan Arang Regional General Hospital Boyolali - Arnanto, Tilawah Juhi; Hermawati; Widodo, Panggah (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
Background: Stroke is a brain disease that attacks the brain suddenly and causes impaired nerve function, caused by blockage of blood vessels and lack of oxygen in the blood to the brain. Poor blood flow in stroke patients results in hemodynamic disorders, including decreased oxygen saturation. One of the independent nursing actions to increase oxygen saturation is to give a 30-degree head-up position. Objective: To determine the results of applying a head-up position of 30 degrees in increasing oxygen saturation in stroke patients in the Emergency Room of Pandan Arang Boyolali Hospital. Methods: This research uses a descriptive method (case study). Results: Oxygen saturation before applying the head-up position, 30 degrees in both respondents, was included in the mild hypoxia category. After applying a head-up position of 30 degrees in both respondents, oxygen saturation was included in the normal category. Conclusion: There are differences in oxygen saturation results before and after applying the 30-degree head-up position in stroke patients.